2006
DOI: 10.1038/sj.emboj.7601155
|View full text |Cite
|
Sign up to set email alerts
|

Tracking of controlled Escherichia coli replication fork stalling and restart at repressor-bound DNA in vivo

Abstract: We report an efficient, controllable, site-specific replication roadblock that blocks cell proliferation, but which can be rapidly and efficiently reversed, leading to recovery of viability. Escherichia coli replication forks of both polarities stalled in vivo within the first 500 bp of a 10 kb repressor-bound array of operator DNA-binding sites. Controlled release of repressor binding led to rapid restart of the blocked replication fork without the participation of homologous recombination. Cytological tracki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
131
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(143 citation statements)
references
References 32 publications
12
131
0
Order By: Relevance
“…Repressors bound to arrays of operators have been found to block the progression of the replisome in Escherichia coli (Possoz et al 2006). We observed a similar replication roadblock in B. subtilis (Supplemental Fig.…”
Section: Tetr-gfp Is Stripped Off Teto Arrays During Translocationsupporting
confidence: 62%
See 1 more Smart Citation
“…Repressors bound to arrays of operators have been found to block the progression of the replisome in Escherichia coli (Possoz et al 2006). We observed a similar replication roadblock in B. subtilis (Supplemental Fig.…”
Section: Tetr-gfp Is Stripped Off Teto Arrays During Translocationsupporting
confidence: 62%
“…However, some DNA-binding proteins have very high affinity for their cognate binding sites. In fact, in some instances these interactions are sufficient to impede the movement of a translocating complex as strong as the replisome (Possoz et al 2006). The biophysical data presently available for either FtsK or SpoIIIE do not allow us to estimate whether these enzymes could displace proteins tightly bound to DNA.…”
mentioning
confidence: 92%
“…We have previously shown that tight binding of fluorescent fusions of either TetR or LacI to arrays of their cognate operators can be achieved when they are expressed in the absence of their inducers (AT and IPTG, respectively) and results in replication blockage at the array (46). Furthermore, replication restarts rapidly upon relief of these tight repressorbinding events.…”
Section: Resultsmentioning
confidence: 99%
“…5C). The following contrasting results were reported regarding the stability of E. coli replisomes: the replisome blocked by an array of repressor-operator complexes loses the ability to continue replication with a half-life of 4 -6 min in vitro (55), whereas it retains the ability to resume replication upon removal of the block for several hours in vivo (56). The dissociation of stalled DnaB from DNA observed in the present study accounts at least in part for the inactivation of the replisome in vitro, although the in vitro half-lives of stalled replisome (4 -6 min) and DnaB (36 min) differ considerably.…”
Section: Discussionmentioning
confidence: 97%